Stereotactic Radiosurgery for Vestibular Schwannoma Outcomes in Patients With Perfect Word Recognition—A Retrospective Cohort Study. Issue 5 (June 2021) - Fouad, Ayman; Tran, Emma D.; Feng, Austin Y.; Alyono, Jennifer C.; Ma, Yifei; Blevins, Nikolas H.; Jackler, Robert K.; Santa Maria, Peter L.
Abstract : Objectives: To investigate tumor control rate and hearing outcomes following stereotactic radiosurgery (SRS) for vestibular schwannoma (VS) cases with perfect (100%) word recognition score (WRS). Study Design: A retrospective cohort study. Setting: Tertiary referral center. Patients: Inclusion criteria were receiving primary SRS, a pretreatment WRS of 100%, and availability of both pre- and posttreatment audiometric data for evaluation. Intervention: SRS delivered by Cyberknife. Main Outcome Measures: Tumor growth rates and audiological outcomes after SRS. Results: The cohort consisted of 139 patients, with more than 1-year follow-up (mean 6.1 yrs). SRS tumor control rate was 87% for the whole cohort. Growth before SRS was documented in 24% (n = 34 of 139). The proportion of sporadic VS cases who maintained hearing (decline <10 dB of pure-tone audiometry or <20% of WRS) at 3 years was 50%, at 5 years was 45%, and at 10 years was 42%. In multivariate analysis, increased age was found to be predictive of increased hearing loss ( p = 0.03), while the following factors were shown not to be significant: sex ( p = 0.5), tumor size ( p = 0.2), pre-SRS tumor growth ( p = 0.5), and target volume ( p = 0.42). Conclusions: Among patients with VS who had perfect WRS and underwent SRS, the overall tumor control rate was 87% comparable to observation. Hearing maintenance and preservation of "serviceable" hearing rates after 5 years in VS patients with perfect WRS treated by SRS is less than that when comparing to similar observation cohorts. Given this finding we do not advocate using SRS to preserve hearing, over observation, in tumors with perfect WRS.